2003
DOI: 10.1016/j.ajodo.2003.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of early orthodontic treatment with the twin-block appliance: a multicenter, randomized, controlled trial. Part 2: psychosocial effects

Abstract: The aims of this project were to evaluate whether early orthodontic treatment with the Twin-block appliance for the developing Class II Division 1 malocclusion resulted in any psychosocial benefits. This multicenter trial was carried out in the United Kingdom, with 174 children aged 8 to 10 years with Class II Division 1 malocclusions randomly allocated to receive treatment with Twin-block appliances or to an untreated control group. Data were collected at the start of the study and 15 months later. Results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
3
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(84 citation statements)
references
References 13 publications
(15 reference statements)
1
73
3
7
Order By: Relevance
“…We believe, therefore, it is unrealistic to expect that major long term changes in psychological well-being could be demonstrated . One randomised controlled trial did find a short term improvement in self-concept when children with a class II division 1 malocclusion were treated early (aged 8 to 10) compared with an untreated control; 30 however other studies have found that orthodontic treatment has no effect on the psychological well-being of individuals, and self-esteem in particular, over the long term. [31][32][33] This has not been a surprising finding to others either.…”
Section: Psychological Well-beingmentioning
confidence: 99%
“…We believe, therefore, it is unrealistic to expect that major long term changes in psychological well-being could be demonstrated . One randomised controlled trial did find a short term improvement in self-concept when children with a class II division 1 malocclusion were treated early (aged 8 to 10) compared with an untreated control; 30 however other studies have found that orthodontic treatment has no effect on the psychological well-being of individuals, and self-esteem in particular, over the long term. [31][32][33] This has not been a surprising finding to others either.…”
Section: Psychological Well-beingmentioning
confidence: 99%
“…Class II division 1 malocclusion has been reported to be associated with less enhanced self-concept and a greater number of negative social experiences. 21 Children with Class III malocclusion have the poorest masticatory efficiency and ability, followed by those with Class II and Class I malocclusion. 22 In the present study, the Class II malocclusion group included only adolescents with Class II division 1 malocclusion because Class II division 2 is an infrequent occurrence (0.4%).…”
Section: Discussionmentioning
confidence: 99%
“…While this modality of treatment conferred early clinical and psychological benefits to the patient, 13,14 it had the disadvantages of longer treatment time, greater overall cost and patient burnout in later stages of treatment. 15 Late treatment with the twin block starting during or slightly after the onset of the peak in mandibular growth appears to be more effective than early treatment, as it induces more favorable mandibular skeletal modifications.…”
Section: Discussionmentioning
confidence: 99%